Jenis-jenis Jamur pada Rimpang Kunyit (Curcuma domestica Val.) di Perkebunan Kunyit Kecamatan Nanga Tayap - Rahmawati, Mirawati, Siti Khotimah (Universitas Tanjungpura, 2016)
Turmeric production in West Kalimantan are still have any problems, especially in Nanga Tayap district, Ketapang regency. One of the problem is decay in turmeric rhizome which is caused by fungi. This study aims to determine the type of fungi that can be found in turmeric rhizome infected in turmeric plantation of Nanga Tayap district. The method that used in sampling was purposive sampling and the isolation by direct planting. The result of the study shows that there are two types of fungi in turmeric rizhome isolated fromturmeric plantation, they are Acremonium sp. K3K and Penicillium exspansum K5K species.